2019
DOI: 10.5812/jamm.88005
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Aspects and Outcome of Hematological Malignancies at the Military Hospital of Antananarivo, Madagascar

Abstract: Background: Currently, the prognosis of hematological malignancies continues to improve in developed countries. In developing countries, such as Madagascar, data on hematological malignancies treatment and outcome are often rare, incomplete, or nonexistent. Until 2011, there was only one cancer center in Madagascar. The Medical Oncology Unit of the Military Hospital of Antananarivo, Madagascar, managed hematological malignancies since December 2012. This pathology represents there the fourth most frequent canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In our study, the sex ratio was 0.25%. This result is comparable to various Malagasy and African studies [2,3,5]. They would be linked to the predominance of gynecological cancers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the sex ratio was 0.25%. This result is comparable to various Malagasy and African studies [2,3,5]. They would be linked to the predominance of gynecological cancers.…”
Section: Discussionsupporting
confidence: 90%
“…Randriamalala's study in southern Madagascar revealed 50 cases of cancer in 15 months from October 1, 2016 to December 31, 2017 [3]. Hasiniatsy's study in the capital showed 181 cases during 2013 [2]. This variation would be related to the number of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In Madagascar, given the absence of a cancer registry, epidemiological data on these cancers come mainly from the capital's hospitals, where colorectal cancers are the most frequent. 2,3 To our knowledge, no epidemiological studies of gastrointestinal cancers have been carried out in the province of Fianarantsoa. The aim of the study was to describe the epidemiological aspect of gastrointestinal cancers at the University Hospital of Tambohobe Fianarantsoa.…”
Section: Introductionmentioning
confidence: 99%
“…8 In the Malagasy literature, we found only two studies on hematological malignancies: the first was about their odontostomatological manifestations at Joseph Ravoahangy Andrianavalona Teaching Hospital (CHU JRA) and the second was about their therapeutic and evolutionary aspects at the Military Hospital of Antananarivo. 9,10 No previous studies have examined either the epidemiology or clinical manifestations of all hematological malignancies in one center in Madagascar. Thus, we aimed to describe the epidemiology and clinical aspects of malignant hemopathies observed at the Medical Oncology Unit of the Military Hospital of Antananarivo.…”
Section: Introductionmentioning
confidence: 99%